Interventions for Early-Stage Pericoronitis: Systematic Review of Randomized Clinical Trials - Tânia Oppido Schalch; Ana Luiza Cabrera Martimbianco; Marcela Leticia Leal Gonçalves; Lara Jansiski Motta; Elaine Marcilio Santos; Rebeca Boltes Cecatto; Sandra Kalil Bussadori; Anna Carolina Ratto Tempestini Horliana (MDPI AG, 2022)
Background: To investigate the efficacy and safety of interventions for early stage pericoronitis. Methods: We searched for randomized controlled trials (RCTs) in databases from inception to July 2020, without language restriction. RCTs assessing adolescents and adults were included. Results: Seven RCT with clinical diversity were included, so, it was not possible to conduct meta-analyses. Individual study data showed an improvement in oral health quality of life in favor of topical benzydamine versus diclofenac capsule (Mean difference (MD) −1.10, 95% Confidence interval (CI) −1.85 to −0.35), and no difference between topical benzydamine and flurbiprofen capsule (MD −0.55 95% CI −1.18 to 0.0). There was no difference between diclofenac and flurbiprofen capsules (MD 0.55, 95% CI −0.29 to 1.39). An imprecise estimate of effects was found for all outcomes, considering (i) oral versus topic pharmacological treatment, (ii) different oral pharmacological treatments, (iii) pharmacological treatment associated with laser versus placebo laser, (iv) pharmacological treatment associated with different mouthwashes, and (v) conventional treatment associated to antimicrobial photodynamic therapy versus conventional treatment, with low to very low certainty of evidence. Conclusions: Until future well-designed studies can be conducted, the clinical decision for early stage pericoronitis should be guided by individual characteristics, settings and financial aspects.